Legal Counseling to Prevent Domestic Violence by Young Indonesian Army Soldiers Creates a Sukinah Bhawantu Family - Wijaya, Dewa Gde Danansasmita; Lukman, Dwi Ratna Kamala Sari; Andriani, I Gusti Ayu Agung; Saridewi, Desak Putu; Rencani, Ni Ketut; Surata, I Ketut; Dikta, Putu Gede Asnawa (LPPM Universitas Dhyana Pura, 2025)
Abstract Domestic violence (DV) is a crime that still frequently occurs in society, yet many victims are reluctant to report it due to legal misunderstandings or social pressure. Domestic violence is not only a moral issue but also a criminal offense. This article analyzes the dangers and sanctions of domestic violence for young Indonesian Army soldiers. The purpose of this study is to increase the understanding of New Soldiers regarding the criminal law aspects related to domestic violence based on Law No. 23 of 2004, as a phenomenon that occurs in society Methods: The activity method includes counseling and interactive discussions at each Srada Bhakti activity. These activities are expected to empower new, unmarried soldiers to contribute to the elimination of domestic violence. The findings of this program aim to provide in-depth insight into Law No. 23 of 2004 concerning the Elimination of Domestic Violence, combined with the principles of Dharma in Hindu teachings that emphasize ahimsa (anti-violence), obligations between husband and wife, and the important value of harmony in the family for young Hindu soldiers. The Dharma Grehasta Counseling Program and Family Mediation This program is directed at developing young soldiers in living a household life in accordance with the principles of Grihastha Ashrama (stages of family life in the Hindu tradition). The